2013
DOI: 10.1007/s10067-013-2450-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis reactivation in patients with rheumatic diseases after immunosuppressive therapy—a report of long-term follow-up of serial cases and literature review

Abstract: The aims of this paper are to report hepatitis B virus reactivation in 12 patients with rheumatic disease undergoing immunosuppressive therapy and to evaluate whether pre-emptive antiviral therapy is necessary in patients receiving disease-modifying anti-rheumatic drugs. From January 2008 to March 2012, a total of 12 HBV-infected patients with rheumatic diseases were consecutively enrolled in the long-term follow-up. Liver function, HBV DNA, and serum aminotransferase level were tested during the follow-up. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 41 publications
(40 reference statements)
0
35
0
5
Order By: Relevance
“…Similar to those using corticosteroids, reports of HBVr among patients with ARDs receiving IMD monotherapy are scarce, as the majority of them also received corticosteroids [28]. A recent prospective study found that the HBVr occurred in four of 211 (1.89%) patients with RA who were HBsAgþ or HBsAgÀ/anti-HBcþ and received cDMARD therapy without antiviral prophylaxis.…”
Section: Conventional Immunosuppressive Agentsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to those using corticosteroids, reports of HBVr among patients with ARDs receiving IMD monotherapy are scarce, as the majority of them also received corticosteroids [28]. A recent prospective study found that the HBVr occurred in four of 211 (1.89%) patients with RA who were HBsAgþ or HBsAgÀ/anti-HBcþ and received cDMARD therapy without antiviral prophylaxis.…”
Section: Conventional Immunosuppressive Agentsmentioning
confidence: 94%
“…The reactivation occurred between 1 and 15 months post cDMARD administration [8]. A recent review found a prevalence of HBVr in 10 of 224 (4.46%) patients with rheumatic disease being treated with cDMARDs, eight of whom were given methotrexate (MTX) [28]. Another study of HBVr was performed in 288 patients with SLE receiving corticosteroids and cIMDs.…”
Section: Conventional Immunosuppressive Agentsmentioning
confidence: 98%
“…In a prospective study of patients treated for nonHodgkin's lymphoma, lamivudine therapy started when ALT elevation was detected did not change the natural course of HBVr; 2 patients in this cohort died despite lamivudine use at the onset of HBVr [8] . Numerous case reports and series describe death due to liver failure despite the introduction of lamivudine at the onset of HBVr [82][83][84][85][86] . Only a few cases of successful treatment of HBVr with entecavir have been published [87][88][89] .…”
Section: Management Of Hbvrmentioning
confidence: 99%
“…Finally, Xuan et al [63] have reviewed 30 cases of reactivation after steroids, in monotherapy or combined with other therapies, in 144 patients with rheumatic diseases. The mean time to reactivations was 9.8 mo.…”
Section: Hbv Reactivations In Patients With Inflammatory Diseasesmentioning
confidence: 99%
“…Adapted from Xuan et al [63] . CHB: Chronic hepatitis B, inactive carriers included; RS: Resolved infection; HBV: Hepatitis B virus.…”
Section: Hbv Reactivations (N )mentioning
confidence: 99%